Leishmania infection alters macrophage and dendritic cell migration in a three-dimensional environment - Luz, Yasmin; Rebouças, Amanda; Bernardes, Carla Polyana O. S.; Rossi, Erik A.; Machado, Taíse S.; Souza, Bruno S. F.; Brodskyn, Claudia Ida; Veras, Patricia S. T.; dos Santos, Washington L. C.; de Menezes, Juliana P. B. (Frontiers in Cell and Developmental Biology, 2023)
Leishmaniasis results in a wide spectrum of clinical manifestations, ranging from skin lesions at the site of infection to disseminated lesions in internal organs, such as the spleen and liver. While the ability of Leishmania-infected host cells to migrate may be important to lesion distribution and parasite dissemination, the underlying mechanisms and the accompanying role of host cells remain poorly understood. Previously published work has shown that Leishmania infection inhibits macrophage migration in a 2-dimensional (2D) environment by altering actin dynamics and impairing the expression of proteins involved in plasma membrane-extracellular matrix interactions. Although it was shown that L. infantum induces the 2D migration of dendritic cells, in vivo cell migration primarily occurs in 3-dimensional (3D) environments. The present study aimed to investigate the migration of macrophages and dendritic cells infected by Leishmania using a 3-dimensional environment, as well as shed light on the mechanisms involved in this process. Following the infection of murine bone marrow-derived macrophages (BMDM), human macrophages and human dendritic cells by L. amazonensis, L. braziliensis, or L. infantum, cellular migration, the formation of adhesion complexes and actin polymerization were evaluated. Our results indicate that Leishmania infection inhibited 3D migration in both BMDM and human macrophages. Reduced expression of proteins involved in adhesion complex formation and alterations in actin dynamics were also observed in Leishmania-